KEANEKARAGAMAN DAN KEMELIMPAHAN COLLEMBOLA DI SEKITAR RIZOSFER TANAMAN BUNGA MAWAR, MELATI, DAN KEMBANG KERTAS DI TAMAN NGROWO BENING MADIUN - Pebianti Geovani; Leo Eladisa Ganjari; Christianto Adhy Nugroho (Biospektrum Jurnal Biologi, 2023)
Collembola is an organism that is beneficial to the soil because it supports plant life in the soil, plays an important role as a modifier of soil organic matter and improves soil physical properties. The purpose of this study was to determine the diversity and abundance of Collembola around the rhizosphere of Rosa hybrida, Jasminum sambac, and Zinnia elegans plants in Taman Ngrowo Bening Madiun. Soil sampling was carried out 3 times in repetition, soil sampling using a soil drill at 3 locations, namely around the rhizosphere of Rosa hybrida plants, rhizosphere of Jasminum sambac plants, and rhizosphere of Zinnia elegans plants. The results of the study found a diversity of 6 species of Collembola including Lobella sp, Hypogastrura sp, Isotomurus sp, Heteromurus sp, Orchesella sp, and Pseudosinella sp. The highest abundance value was found around the rhizosphere of Jasminum sambac plants, namely 36 individuals. Around the rhizosphere of Rosa hybrida plants there are 19 individuals and around the rhizosphere of Zinnia elegans plants there are 33 individuals with a total abundance of 88 individuals. The Collembola diversity index around the rhizosphere of Rosa hybrida was H'= 0.68063, in the rhizosphere of Jasminum sambac H'= 1.24794, and in the rhizosphere of Zinnia elegans H'= 0.66161. Keywords: Collembola, Rosa hybrida, Jasminum sambac, Zinnia elegans